The Problematics Implementation of Law and Regulations Testing in Indonesia - suparto suparto (Yuridika, 2022)
One of the results of the constitutional change, particularly during the 3rd amendment in 2001 is related to the arrangement of judicial powers exercised by two state institutions; the Supreme Court (MA) and the Constitutional Court (MK). Both as executors of judicial power are given different duties regarding the object of testing a statutory regulation. The Supreme Court is based on Article 24A Paragraph (1) of The Constitution of 1945 relating to the authority to test the legality of statutory regulations under the law against laws, while the Constitutional Court is given the authority to examine constitutionality of laws against the Constitution of 1945  based on Article 24C Paragraph (1) of the Constitution of 1945. Based on the research, it was found that the two state institutions, namely MA and MK, are both given authority in examining the legislation causing problems such as the following : (1). Potentially raises the insynchronity between the Supreme Court's ruling and the Constitutional Court's ruling. (2). The Supreme Court's decision is considered by the Constitutional Court in making the decision. (3). There is a temporary suspension of testing in the Supreme Court (MA). This can affect the institutional relationship between judicial institutions, the image and the authority of the court's rulings, can also cause legal uncertainty so that it will harm the interests of the justice-seeking community.